Amino acid nutrition of salmonids: Dietary requirements and bioavailability - Lall S.P.; Anderson S. (Mediterranean fish nutrition, 2005)
The amino acid (AA) requirements of salmonid fishes and the shortcomings of methods used to estimate AA requirement are briefly reviewed. The reported essential AA requirements for certain AA of salmon and rainbow trout do not always agree well. For a proper feed formulation, prudent analogy of the reported AA requirement values and the estimates of AA bioavailability data from plant and animal protein sources are necessary. The apparent and true AA (TAA) availability values have been published for only a few animal and protein sources. TAA values give a better indication of the biological value, specifically for those feed ingredients with relatively low protein content. Further research on a better estimate of feedstuffs amino acid bioavailability, as well as maintenance requirement and protein accretion of fish, will result in the more efficient use of alternate protein sources to fish meal in salmonid feeds and lower nitrogenous waste.
Workshop on Mediterranean Fish Nutrition, 2002/06/01-02, Rhodes (Greece)